Bishops and bailiwicks - obstacles to women's political-participation in Ireland - Randall, Vicky; Smyth, Ailbhe (Economic & Social Studies, 1987)
Women are a small minority of political office-holders in Ireland as elsewhere. The authors first provide details of women's representation in different political arenas, before proceeding to identify the principal determinants of women's willingness to seek office - socialisation, domestic constraints and access to appropriate educational and professional qualifications - and the institutional barriers they encounter. Two features of particular relevance in Ireland are the impact of Roman Catholicism on political culture and the role of localism in party politics. So long as these retain their hold there is little prospect of a drama lie increase in women's political representation.
Keywords: Wome in politics - Ireland; Sex discrimination - Ireland